The oxygen isotopic and chemical composition of the primitive Asuka CM chondrites - Kimura, Makoto; Greenwood, Richard C.; Barrat, Jean-Alix; Imae, Naoya; Komatsu, Mutsumi; Yamaguchi, Akira; Noguchi, Takaaki (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object